Hemileia vastatrix: a climate change prospect - Parada Molina, Paulo César; Cerdán Cabrera, Carlos Roberto; Ortiz Ceballos, Gustavo; Cervantes Pérez, Juan; Barradas-Miranda, Víctor Luis (Ecosistemas y Recursos Agropecuarios, 2020)
Hemileia vastatrix, the fungus that causes the most devastating disease of Coffea arabica L. (coffee rust), could increase its altitude distribution due to climate change, causing adverse effects. Therefore, realized a prospecting of the effect of climate change on the incidence of H. vastatrix. This study was conducted out taking data from the coffee growing area of Coatepec, Veracruz, Mexico. The trends of maximum, minimum temperature and climatic extremes indexes (1961-2010) proposed by the Team of Experts on Climate Change Detection and Indices (ETCCDI) were analyzed. Trends were related to conditions suitable for the proliferation of Hemileia vastatrix. The area has experienced an increase in the maximum temperature (0.2 ◦C decade−1 ) and minimum (0.3 ◦C decade−1 ). Annual rainfall and daily intensity have increased, increasing the susceptibility to incidence and severity from coffee rust and other fungal diseases.